Government spending, growth and poverty in rural India - Fan, Shenggen; Hazell, Peter B. R.; Thorat, Sukhadeo (Wiley, 2000)
Using state‐level data for 1970–93, a simultaneous equation model was developed to estimate the direct and indirect effects of different types of government expenditure on ruralpoverty and productivity growth in India. The results show that in order to reduce rural poverty, the Indian government should give highest priority to additionalinvestments in ruralroads and agriculturalresearch. These types of investment not only have much larger poverty impacts per rupee spent than any other government investment, but also generate higher productivity growth. Apart from government spending on education, which has the third largest marginalimpact on ruralpoverty and productivity growth, other investments (including irrigation, soil and water conservation, health, and rural and community development) have only modest impacts on growth and poverty per additional rupee spent.